2009
DOI: 10.18433/j3fw2q
|View full text |Cite
|
Sign up to set email alerts
|

Where is Industry Getting it Wrong? A Review of Quality Concerns Raised at Day 120 by the Committee for Medicinal Products for Human Use during European Centralised Marketing Authorisation Submissions for Chemical Entity Medicinal Products

Abstract: -Purpose. The aim of this study was to identify common trends in the deficiencies identified in the quality part of the dossier during the evaluation of marketing authorisation applications for medicinal products for human use submitted through the EU's centralised procedure. Methods. We analysed all the adopted Day 120 list of questions on the quality module of 52 marketing authorisation applications for chemical entity medicinal products submitted to the European Medicines Agency and evaluated by the Committ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 2 publications
0
20
0
Order By: Relevance
“…To our knowledge this is the first time a review of API quality deficiencies covers all dossiers over such a long time period; the European Directorate for the Quality of Medicines (EDQM) top ten deficiencies documents are based on the contents of a sample of the deficiency letters in each year and the European Medicines Agency (EMA) quality deficiencies publication included questions raised over a period of only two years (16)(17)(18)(19)(20)(21). In addition our study includes the quantification and description of all deficiencies to the level of the CTD subsection; the EDQM reported the ten most frequent groups of deficiencies and in the review of deficiencies raised by EMA these were quantified to the level of the CTD section only (16)(17)(18)(19)(20)(21). Furthermore, to our knowledge this is the first time a study on API quality deficiencies has been performed on APIs intended for generic medicines from emerging markets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge this is the first time a review of API quality deficiencies covers all dossiers over such a long time period; the European Directorate for the Quality of Medicines (EDQM) top ten deficiencies documents are based on the contents of a sample of the deficiency letters in each year and the European Medicines Agency (EMA) quality deficiencies publication included questions raised over a period of only two years (16)(17)(18)(19)(20)(21). In addition our study includes the quantification and description of all deficiencies to the level of the CTD subsection; the EDQM reported the ten most frequent groups of deficiencies and in the review of deficiencies raised by EMA these were quantified to the level of the CTD section only (16)(17)(18)(19)(20)(21). Furthermore, to our knowledge this is the first time a study on API quality deficiencies has been performed on APIs intended for generic medicines from emerging markets.…”
Section: Discussionmentioning
confidence: 99%
“…Limited information is available in the public domain with respect to the actual API deficiencies found by assessors in SRAs, but specific studies have been published by the EDQM (16)(17)(18)(19)(20). There are also two publications on the review of API deficiencies raised by the United States Food and Drug Administration (USFDA) and the EMA (21)(22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since it was a newly implemented measure, deficiencies related to the lack of information regarding the source of the drug substance are unique in the review process for submissions in Taiwan, which were rarely found in the applications submitted to other agencies such as the EMA, 15 the FDA, 10,11 and the WHO. 14 …”
Section: Discussionmentioning
confidence: 99%
“…The presentation of the above-mentioned issues provided an overview on the regulatory considerations for generic drug applications in Taiwan. The similarities in the deficiencies listed in the final quality assessment reports to the common deficiencies observed by the EMA, 15 the FDA, [10][11][12][13] and the WHO 14 might suggest the harmonization of regulatory requirements, while the dissimilarities could reflect the difference in the regulatory framework. Through the analysis of the deficiencies in the present article, applicants will be able to have a clearer outline on the review issues in Taiwan, which may aid the applicants to prepare further informational details for clarification or for the development of a new generic drug product.…”
mentioning
confidence: 99%